2022
DOI: 10.3389/fenvs.2022.998527
|View full text |Cite
|
Sign up to set email alerts
|

How do ecological vulnerability and disaster shocks affect livelihood resilience building of farmers and herdsmen: An empirical study based on CNMASS data

Abstract: Based on the survey data on animal husbandry from 1,689 households in semi-agricultural and semi-pastoral counties in Inner Mongolia, this paper applied the “buffer capacity–organizational capacity-learning capacity” framework to analyze the current livelihood resilience of farmers and herdsmen, as well as the impact of ecological vulnerability and disaster shocks on this resilience. The results show that, first, due to the vicious ecological environment and natural disasters, livelihood resilience among farme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 54 publications
1
8
0
Order By: Relevance
“…External assistance facilitated livelihood provisioning, protection, and promotion for the Sidr case; in contrast, the top-down external interventions that prevailed in the Wenchuan case jeopardized the rural communities LTLR, primarily because of the powers that ignored the local traditional livelihood practice. Findings from this study concur with previous studies on learning capacity (Lade, Walker, and Haider 2020; Yan, Xi, and Weihong 2022), enabling and/or constraining factors (Sina et al 2019b; Pu et al 2021), and external assistance (Imperiale and Vanclay 2020; Shahidullah, Choudhury, and Haque 2020). Additionally, a comparative analysis, in this study, revealed the contextual variability of three themes and identified causes of such variations.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…External assistance facilitated livelihood provisioning, protection, and promotion for the Sidr case; in contrast, the top-down external interventions that prevailed in the Wenchuan case jeopardized the rural communities LTLR, primarily because of the powers that ignored the local traditional livelihood practice. Findings from this study concur with previous studies on learning capacity (Lade, Walker, and Haider 2020; Yan, Xi, and Weihong 2022), enabling and/or constraining factors (Sina et al 2019b; Pu et al 2021), and external assistance (Imperiale and Vanclay 2020; Shahidullah, Choudhury, and Haque 2020). Additionally, a comparative analysis, in this study, revealed the contextual variability of three themes and identified causes of such variations.…”
Section: Discussionsupporting
confidence: 91%
“…A limited number of studies have attempted to measure learning capacity quantitatively in disaster settings, using different indicators. Li et al (2022), for example, have used three indicators to measure learning capacities, such as knowledge transfer capability, exposure to social and cultural norms, and knowledge identification capacity while Yan, Xi, and Weihong (2022) have used four indicators, paying more attention to education. The indicators they have used are the education level of household heads, non-agricultural work experience, information acquisition capability, and education investment.…”
Section: Ltlr: Resilience and Sustainabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, previous studies have also pointed out that the role of household endowment in HLR varies greatly; these differences also provide directions for the improvement of decision-making on adaptation and HLR (Awazi and Quandt, 2021;Dongdong et al, 2022;Li et al, 2022b). For example, in the Three River Headwater Region on the Tibetan Plateau (TP), the low buffer capacity has limited the overall distribution of livelihood resilience, and natural capital is a main factor of this resilience component.…”
Section: Introductionmentioning
confidence: 99%
“…As the core part of the SLA, livelihood capital has become the focus of many studies, mainly involving sustainable livelihoods (Marulanda et al, 2020;Yang et al, 2021;Azumah et al, 2022;Yan et al, 2022), poverty eradication (Zhang et al, 2020;Wang et al, 2021b), and public policy (Hua et al, 2017;Jin et al, 2021), and fruitful research results have been obtained. Subsequently, the five forms of sub-capital have become a popular research tool for quantitative measurement and an entry point for exploring relevant practical problems (Roberts and Yang, 2003;Chen et al, 2013;Zhang C. et al, 2019).…”
Section: Introductionmentioning
confidence: 99%